Digital Readiness and Intention to Adopt Blockchain VAT Systems in Indonesia’s MSME Sector - Nurul Izzah Lubis; Citra Windy Lubis; Haervi Yunira (Jurnal Akuntansi dan Keuangan, 2026)
This study examines Indonesian MSMEs’ intention to adopt a blockchain-based Value Added Tax (VAT) system, with digital literacy as a moderating variable. A structured questionnaire was distributed online and offline to 300 MSME owners across diverse sectors, with 210 complete responses analyzed using SEM-PLS. Findings show that performance expectancy, effort expectancy, hedonic motivation, price value, and habit significantly influence adoption intention, while facilitating conditions and social influence have weaker effects. Digital literacy strengthens the impact of performance and effort expectancy, highlighting its role in enhancing adoption readiness. The study contributes by applying blockchain adoption insights in a novel taxation context and underscores the importance of digital readiness in emerging economies. Practical implications suggest targeted literacy programs and infrastructure support to promote inclusive adoption. Overall, this research provides timely insights for digital tax transformation in Indonesia.